2019
DOI: 10.3390/ijerph16040583
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal in Oligotrophic Reservoir Water by a Mixed Aerobic Denitrifying Consortium: Influencing Factors and Immobilization Effects

Abstract: Nitrogen pollution in reservoirs has received increasing attention in recent years. Although a number of aerobic denitrifying strains have been isolated to remove nitrogen from eutrophic waters, the situation in oligotrophic water environments has not received significant attention. In this study, a mixed aerobic denitrifying consortium screened from reservoir samples was used to remove nitrogen in an oligotrophic denitrification medium and actual oligotrophic source water. The results showed that the consorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…From the above results, CRI.NF, CRI.DNF and CRIC showed higher similarity community structure at the phylum level, compared to those samples from EC and IC. To our knowledge, the main studies of OHN and OAD bacteria are mainly focused on phylum Proteobacteria, Actinobacteria, and Firmicutes (Huang et al 2013;Srivastava et al 2016;Zhou et al 2016;Zhao et al 2017;Wang et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the above results, CRI.NF, CRI.DNF and CRIC showed higher similarity community structure at the phylum level, compared to those samples from EC and IC. To our knowledge, the main studies of OHN and OAD bacteria are mainly focused on phylum Proteobacteria, Actinobacteria, and Firmicutes (Huang et al 2013;Srivastava et al 2016;Zhou et al 2016;Zhao et al 2017;Wang et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…4). The contribution of denitrification to TN and nitrate removal from water has been investigated by other scientists (Gao et al 2010;Wang et al 2019). Sun et al (2015) studied bioceramic immobilized aerobic denitrifier Pseudomonas stutzeri T13, and found that the nitrate removal rate of immobilized strain was higher than the free state under oligotrophic conditions.…”
mentioning
confidence: 99%
“…Letters in Applied Microbiology 70, 263--273 © 2019 The Society for Applied Microbiology significantly faster and higher than that reported for some other strains (Shi et al 2007;Kassim et al 2018;Wang et al 2019). Furthermore, the immobilized cells could be recycled 12 times, which was also much higher than that of nine times reported recently (Wang et al 2019).…”
Section: Resultsmentioning
confidence: 69%
“…As for the total nitrogen removal, our study provides a more economical and effective method for TN removal from wastewater by immobilized cells. It was taken only 1 h for the immobilized P. denitrificans DYTN‐1 to remove the TN in the sewage below 20 mg l −1 (84·1% removal rate), which was significantly faster and higher than that reported for some other strains (Shi et al ; Kassim et al ; Wang et al ). Furthermore, the immobilized cells could be recycled 12 times, which was also much higher than that of nine times reported recently (Wang et al ).…”
Section: Resultsmentioning
confidence: 89%
“…NO 3 − -N and NO 2 − -N could be converted into nitrogen by denitrifiers under anaerobic or anoxic conditions in traditional denitrification theory; four main steps happen in sequence: NO 3 − -N→NO 2 − -N→NO→N 2 O→N 2 [10,11]. Four key reductases, nitrate reductase ( Nap ), nitrite reductase ( NirS or NirK ), nitric oxide reductase ( Nor ), and nitrous oxide reductase (N 2 OR), correspond to these four steps, respectively [12]. Traditional theory holds that the denitrification process is sensitive to dissolved oxygen (DO) concentrations [13,14].…”
Section: Introductionmentioning
confidence: 99%